Relationship between Waist Circumference (Abdomen) and Triglyceride and Low Density Lipoprotein-Cholesterol (LDL-C) Levels in Premenopausal Women - Mutmainnah Abbas; Rosdiana Mus (Halu Oleo University, 2022)
Background: Premenopausal is a period that women will experience before heading to the menopause phase in the age range of 4 5-55 years. In the premenopausal period it is characterized by the instability of the hormone estrogen which will affect lipid metabolism which is closely related to the increase in abdominal fat known as abdominal or central obesity . The instability of the hormone estrogen results in hormonal changes that affect the levels of lipids in the body such as TG and LDL-Chol levels in the blood. Purpose(s): This study aims to determine whether there is a relationship between Waist Circumference (Abdomen) and Triglyceride and Low Density Lipoprotein-Cholesterol (LDL-C) Levels in Premenopausal Women. Methods: This study used an analytical correlative method with a cross-sectional study approach. This study involved 40 research subjects who met the criteria. Results: In the results of the pearson correlation test analysis to determine the relationship between the abdominal waist circle and TG levels in premenopausal women, the results of the p value = 0.351 and the pearson correlation test value = 0.15 were obtained. In the correlation test between waist circumference (abdomen) and LDL- Chol levels in premenopausal women, a value of p = 0.164 with a pearson correlation value of 0.224 was obtained. Conclusion: There is no relationship between Waist Circumference (Abdomen) and Triglyceride and Low Density Lipoprotein-Cholesterol (LDL-C) Levels in Premenopausal Women.Keywords: Premenopause, Waist Circumference, Lipid, Triglycerides, Low Density Lipoprotein